2022
DOI: 10.1155/2022/2371807
|View full text |Cite
|
Sign up to set email alerts
|

GSDME Increases Chemotherapeutic Drug Sensitivity by Inducing Pyroptosis in Retinoblastoma Cells

Abstract: Chemotherapy is an important part of retinoblastoma (RB) treatment. However, the development of drug resistance increases the likelihood of treatment failure. Therefore, increasing the sensitivity of chemotherapeutic drugs is very important. Recent research has explored the relationship between the expression level of gasdermin E (GSDME) and drug sensitivity in RB. Our study found that GSDME expression was significantly reduced in human RB tissues and cell lines. Downregulation of GSDME expression reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…To measure the disruption of the inner membrane barrier function, the membrane integrity dye propidium iodide (PI) was used. PI is a nucleic acid dye that cannot pass through normal membranes owing to their barrier action, but it can dye the nucleus red in necrotic cells with altered membrane permeability [ 32 ]. A graded series of AA concentrations (1 × , 1/2 × , 1/4 × , 1/8 × , 1/16 × MIC) were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…To measure the disruption of the inner membrane barrier function, the membrane integrity dye propidium iodide (PI) was used. PI is a nucleic acid dye that cannot pass through normal membranes owing to their barrier action, but it can dye the nucleus red in necrotic cells with altered membrane permeability [ 32 ]. A graded series of AA concentrations (1 × , 1/2 × , 1/4 × , 1/8 × , 1/16 × MIC) were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that GSDME is downregulated in some human cancers and might act as a tumor suppressor [ 39 , 40 ]. The DNA methylase inhibitor decitabine (5-aza-2'-deoxycytosine) could downregulate the expression of GSDME, thereby preventing the proliferation and colony formation ability of melanoma, gastric cancer and CRC cells, and may reduce the invasive ability of breast cancer cells [ 41 ]. In addition, GSDME is associated with etoposide resistance [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“… 227 , 228 , 229 Meanwhile, pyroptosis occurs in almost all the type of cancer and shows a double‐edged sword effect to cancers, which could either enhance or restrain tumorigenesis. 230 , 231 , 232 , 233 Therefore, we need to deeply explore the specific mechanism of pyroptosis and tumor progression to provide evidence for tumor prevention and treatment (Table 4 ).…”
Section: Pyroptosis and Cancermentioning
confidence: 99%
“…Particularly, pyroptosis induces inflammatory cytokines release, such as IL‐1 and IL‐18, which could induce an inflammatory environment to increase tumor infiltration and promote the likelihood of tumorigenesis and metastasis 227–229 . Meanwhile, pyroptosis occurs in almost all the type of cancer and shows a double‐edged sword effect to cancers, which could either enhance or restrain tumorigenesis 230–233 . Therefore, we need to deeply explore the specific mechanism of pyroptosis and tumor progression to provide evidence for tumor prevention and treatment (Table 4).…”
Section: Pyroptosis and Cancermentioning
confidence: 99%